Sulfate Encapsulation in Supramolecular Structures from L‐Asparagine‐Derived 2, 5‐Diketopiperazine Scaffolds: Anion Binding. Issue 31 (24th September 2014) - Naini, Santhosh Reddy; Lalancette, Roger A.; Gorlova, Olga; Ramakrishna, Kallaganti V. S.; Yadav, Jhillu Singh; Ranganathan, Subramania
Abstract: We report a new sulfate receptor, anchored onto 2, 5‐diketopiperazine units, which results in the formation of two types of supramolecules; one in which the sulfate ion guest fits snugly into extended cavities and the other in which the guest is sandwiched between layers. In each case, the anion is held by six hydrogen bonds from the host. 1 H NMR spectroscopic solution studies enabled the construction of Job plots, and calculation of stoichiometry and association constants. These findings are of possible significance in drug design and for construction of combinatorial libraries. Abstract : We report a new sulfate receptor, anchored onto 2, 5‐diketopiperazine units, which results in the formation of two types of supramolecules; one in which the sulfate ion guest fits snugly into extended cavities and the other in which the guest is sandwiched between layers. In each case, the anion is held by six hydrogen bonds from the host. Job plots and association constants were calculated.